An overview of bus drivers and accident involvement - Md. Rohani, Munzilah; Mohd. Nawi, Nafhah Nabiha; Daniel, Basil David; Aman, Mohd. Yusri; Buhari, Rosnawati; Ambak, Kamaruddin (American Scientific Publishers, 2018)
Common causes of bus accidents are similar to those causing other vehicular accidents. Bus accidents are rare, but they can cause major life disruption and unexpected expenses. Behavior of the bus driver does not only affect passengers comfort, but are also associated with the risk of road crash. In most driving situations, variations of driving behaviour and whether they get involved with accidents or not are influenced by various factors such as human factor, road and traffic situation, working environment, etc. This paper reviews these factors from previous research.